Memahami Kesilapan Pelajar dalam Membentuk Penghujahan Saintifik (Sains Humanika, 2014)
Scientific argumentation is given the main emphasis in science education due to the fact that it is able to promote students’ reasoning skills and content knowledge. Literatures have shown that students have various difficulties in generating scientific arguments. Thus, this study aims to investigate errors made by students in constructing scientific arguments. The study conducted was a combination of qualitative and quantitative research to examine in-depth the errors made by students in scientific argumentation. A total of 75 form four students from Pasir Gudang District participated in this study. Data were collected from students’ responses in Scientific Argumentation Test (UPS) and interviews. Data were analyzed using SPSS Version 19.0 software and content analysis technique. Results showed that the most frequent errors exist in students’ arguments is from category argument with irrelevant grounds, followed by argument with alternative frameworks. Ground indicates a combination of the elements data, warrant and backing that supports an argument. Besides, chi-squared test showed that there was a significant difference between the categories of arguments constructed by students. Hence, the teaching of science in school should focus on argumentative activities that enhance the mastery of scientific argumentation in order to eliminate students’ alternative frameworks and foster the understanding of scientific concepts.
Keywords: Acids and bases; alternative framework; neutralization; properties of acids and bases; scientific argumentation; strength of acids and bases